Long-term effects of Dance for PD® on self-efficacy among persons with Parkinson's disease. Issue 1 (2nd January 2018) - McRae, Cynthia; Leventhal, David; Westheimer, Olie; Mastin, Taylor; Utley, Jared; Russell, Daniel
Abstract: Background: Dance for Parkinson's Disease or Dance for PD® (DfPD) classes were developed by the Mark Morris Dance Group and Brooklyn Parkinson Group in 2001. This exploratory study examined long-term effects of DfPD on non-dance activities outside the studio, functional mobility, self-efficacy, and quality of life (QoL). Methods: Individuals in four well-established DfPD classes completed a survey regarding perceived impact of DfPD. Response rate was 55%; 61 completed surveys were included in analyses. Results: Responses indicated that DfPD clearly impacts daily functioning outside the studio. Results of regression analyses indicated that functional mobility and self-efficacy were associated with QoL. Mediation analyses indicated that one way in which higher levels of functional mobility influence QoL is by enhancing self-efficacy of the PD participants. Conclusions: Because of the direct effect of self-efficacy on QoL, results suggest future research focus on self-efficacy as well as functional mobility and mood in dance research related to PD.